TuBaFrost 5: multifunctional central database application for a European tumor bank. - Isabelle, M; Teodorovic, I; Morente, M; Jaminé, D; Passioukov, A; Lejeune, S; Therasse, P; Dinjens, W; Oosterhuis, J; Lam, K; Oomen, M; Spatz, A; et al. (2006)
Developing a tissue bank database has become more than just logically arranging data in tables combined with a search engine. Current demand for high quality samples and data, and the ever-changing legal and ethical regulations mean that the application must reflect TuBaFrost rules and protocols for the collection, exchange and use of tissue. To ensure continuation and extension of the TuBaFrost European tissue bank, the custodianship of the samples, and hence the decision over whether to issue samples to requestors, remains with the local collecting centre. The database application described in this article has been developed to facilitate this open structure virtual tissue bank model serving a large group. It encompasses many key tasks, without the requirement for personnel, hence minimising operational costs. The Internet-accessible database application enables search, selection and request submission for requestors, whereas collectors can upload and edit their collection. Communication between requestor and involved collectors is started with automatically generated e-mails.